Taxonomic studies on some coprophilous species of Conocybe from India - Atri, N S; Kaur, Munruchi; Kaur, Amandeep (Mushroom Research, 2012)
The present paper deals with the collections of Conocybe Fayod from various dung localities of Punjab. The four coprophilous species of this genus, namely, C. subxerophytica var. subxerophytica Singer & Hauskn., C. subxerophytica var. brunnea Hauskn., C. uralensis Hauskn., Knudsen & Mukhin and C. apala (Fr.) Arnolds are taxonomically described alongwith the type of dung they were associated with. These species are recorded for the first time from India.